How Art Therapy Can Assist College Students from Diverse Backgrounds in Overcoming Cultural Differences - Kim, Narae (My University, 2017)
The opportunity for international students on university campuses to participate in art therapy is a beneficial student service. Through art therapy interventions, students may gain pride and confidence in their academics as well as obtain successful campus lives with concrete aims and goals. Culturally diverse students may confront culture shock in higher education school systems. This paper demonstrates how art therapy sessions that were provided on campus helped students to better understand their circumstances, to build self-esteem, and to achieve therapeutic goals to enhance their wellbeing. The author provides three case examples that use a combination of art therapy and counseling techniques to assist international college students in coping.
Keywords: college students; depression; multiculturalism; art therapy; Visual Arts